Conference highlights: The 81st Annual (Virtual) conference of the American diabetes association: June 25–29, 2021 - Suliman, Mohamed; Mohammed, Nagi (Journal of Diabetes and Endocrine Practice, 2021)
The American Diabetes Association (ADA) annual conference is the most notable annual event in diabetes. Like many conferences in 2020 and 2021, it was held virtually due to the COVID-19 pandemic. In this highlights summary, we selected the sections that we felt are particularly relevant to practicing clinicians. The results of several long-awaited studies were released. These include the GRADE study, SURPASS, and STEP studies. The first ADA-European Association for the Study of Diabetes consensus on the management of type 1 diabetes was also aired during the conference. Besides, the AMPLITUDE-O study with new data on the cardiovascular and renal effects of Efpeglenatide was published. The role of Teplizumab for the prevention of type 1 diabetes and Volagidemab in patients with type 1 diabetes were discussed. Furthermore, the PROMISE study on the safety and accuracy of next-generation 180 days implantable continuous glucose monitoring systems was published. New news included advancing the role of glucagon in treating and preventing severe hypoglycemia. Furthermore, the Effects on heart failure with preserved ejection fraction from a pooled analysis of SOLOIST and SCORED studies were presented. Finally, data on Dapagliflozin in COVID-19 (DARE-19) and the STRENGTH versus REDUCE-IT studies were compared and contrasted. We hope to present a concise summary of the conference highlights for those who missed the live event.
Keywords: American Diabetes Association; diabetes; education; glucagon; research; trials